2006
DOI: 10.1002/humu.9458
|View full text |Cite
|
Sign up to set email alerts
|

Biological effects of four PSEN1 gene mutations causing Alzheimer disease with spastic paraparesis and cotton wool plaques

Abstract: † Cecile Dumanchin and Isabelle Tournier contributed equally to this work. Communicated by Claude FerecWe describe the biological consequences on PSEN1 exons 8 or 9 splicing and Aβ peptides production of four PSEN1 mutations associated with a phenotypic variant of Alzheimer disease, which includes cotton wool plaques and spastic paraparesis (CWP/SP). Two of these mutations (c.869-22_869-23ins18 and c.871A>C, p.T291P) are novel mutations located in intron 8 and exon 9, respectively. The c.869-22_869-23ins18 mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 29 publications
0
38
0
Order By: Relevance
“…The results of ELISA analysis revealed that the level of both Aβ isoforms was significantly elevated in the neurons of AD-iENP derived from two fAD-FB populations with the PSEN1 mutation (AD2 and AD3, Figure 7C) compared with the control-iENP-derived neurons. The Aβ42/Aβ40 ratio was also increased in the fAD-iENP-derived neurons induced from fAD-FBs with the PSEN1 E184D mutation (AD2), although no significant increase in the Aβ42/Aβ40 ratio was detected in the fAD-iENP-derived neurons induced from another fAD-FB population with the PSEN1 P264L mutation (AD3), which was previously reported to be associated with a slight increase in the Aβ42/Aβ40 ratio in PSEN1 P264L-overexpressing cells (Dumanchin et al., 2006). To investigate pTAU pathologies in the AD-iENP-derived neurons, we first subjected AD1- and control-iENP-derived neurons to ICC analysis with an antibody recognizing pTAU (AT8); in this way, we readily detected pTAU in the processes of certain TUJ1 + neurons and observed patched pTAU aggregates in the cell body of AD-iENP-derived neurons, as previously reported in the cortex of AD patients and AD-iPS-derived neurons (Figure 7Da) (Choi et al., 2014, Goedert et al., 1993).…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…The results of ELISA analysis revealed that the level of both Aβ isoforms was significantly elevated in the neurons of AD-iENP derived from two fAD-FB populations with the PSEN1 mutation (AD2 and AD3, Figure 7C) compared with the control-iENP-derived neurons. The Aβ42/Aβ40 ratio was also increased in the fAD-iENP-derived neurons induced from fAD-FBs with the PSEN1 E184D mutation (AD2), although no significant increase in the Aβ42/Aβ40 ratio was detected in the fAD-iENP-derived neurons induced from another fAD-FB population with the PSEN1 P264L mutation (AD3), which was previously reported to be associated with a slight increase in the Aβ42/Aβ40 ratio in PSEN1 P264L-overexpressing cells (Dumanchin et al., 2006). To investigate pTAU pathologies in the AD-iENP-derived neurons, we first subjected AD1- and control-iENP-derived neurons to ICC analysis with an antibody recognizing pTAU (AT8); in this way, we readily detected pTAU in the processes of certain TUJ1 + neurons and observed patched pTAU aggregates in the cell body of AD-iENP-derived neurons, as previously reported in the cortex of AD patients and AD-iPS-derived neurons (Figure 7Da) (Choi et al., 2014, Goedert et al., 1993).…”
Section: Resultsmentioning
confidence: 65%
“…As proof of principle, we induced iENPs from the FBs of AD and HD patients and demonstrated that the diseased iENPs and their neuronal derivatives exhibited pathological features of HD and AD (Choi et al., 2014, Jackson and Bartek, 2009). For example, our data showed a dramatic increase of Aβ variants and Aβ42/Aβ40 ratio and increased pTAU expression in the AD-iENPs-derived neurons; expression of pTAU could be reduced by GSK3β inhibitors, suggesting the AD-iENP-derived neurons recapitulate some, if not all, of the AD pathological features (Choi et al., 2014, Dumanchin et al., 2006). Several lines of evidence have indicated that stress factors can cause DNA damage and increase profound neuronal death in cells derived from HD patients (Jackson and Bartek, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The CWP/SP PS1 mutants for these studies were identified by literature search and then generated by site-directed mutagenesis. The PS1-FAD constructs selected for these experiments were: L85P (SP, plaque pathology unknown) [32], G217D (CWP, Parkinsonism) [33], ΔE8 (CWP) [24], E280G (CWP/SP) [34, 35], T291P (CWP/SP) [36], N405S (CWP/SP) [37], and L420R (CWP) [38]. As in previous experiments [21, 22], the constructs were co-transfected with EGFP expression plasmid and WT PS1 construct was used as a positive control.…”
Section: Resultsmentioning
confidence: 99%
“…PSEN1 mutations appear to increase the ratio of Aβ 42 to Aβ 40 , thereby resulting in a change in function that leads to reduced γ-secretase activity [39]. Enhanced Aβ 42 production has been further confirmed in cell transfection studies for certain mutations, including P264L [40]. It has been suggested that deposition of Aβ 42 may be an early preclinical event in PSEN1 mutation carriers [41].…”
Section: Discussionmentioning
confidence: 99%